The R2R3-MYB Factor FhMYB5 From Freesia hybrida Contributes to the Regulation of Anthocyanin and Proanthocyanidin Biosynthesis - Li, Yueqing; Shan, Xiaotong; Zhou, Liudi; Gao, Ruifang; Yang, Song; Wang, Shucai; Wang, Li; Gao, Xiang (Frontiers in Plant Science, 2019)
The flavonoids are important and nourishing compounds for plants and human. The transcription regulation of anthocyanin and proanthocyanidin (PA) biosynthesis was extensively studied in dicot compared with monocot plants. In this study, we characterized the functionality of an R2R3-MYB gene FhMYB5 from the monocotyledonous flowering plant of Iridaceae, Freesia hybrida. Multiple sequence alignment and phylogenetic analysis implied that FhMYB5 was clustered into grapevine VvMYB5b subclade. Correlation analysis indicated that the spatio-temporal expression patterns of FhMYB5 coincided well with anthocyanin and PA accumulations in Freesia per se. Furthermore, transient transfection assays in Freesia protoplasts revealed that the late flavonoid biosynthetic genes (e.g., DFR and LDOX) were slightly up-regulated by FhMYB5 alone, whereas both early and late biosynthetic genes were significantly activated when FhMYB5 were co-infected with either of the two IIIf clade bHLH genes, FhTT8L and FhGL3L. Moreover, these results were further confirmed by co-transfection of FhMYB5 with either of the bHLH genes aforementioned into protoplasts expressing GUS reporter gene driven by Freesia promoters. In addition, the overexpression of FhMYB5 in tobacco and Arabidopsis could also significantly up-regulate the expression of genes participating in the general flavonoid pathway. In conclusion, FhMYB5 was proved to function in the general flavonoid pathway in Freesia. The results implied a function conservation of flavonoid biosynthesis related MYB regulators in angiosperm plants.